2009
DOI: 10.1007/s00417-009-1174-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual comparison after combined phaco-trabecular aspiration in pairs of pseudoexfoliative eyes

Abstract: The postoperative outcome in an eye after combined phaco-trabecular aspiration is predictive for the second eye. If this procedure succeeded in the first eye, the prognosis for the same strategy in the fellow eye is also good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(19 reference statements)
2
10
0
Order By: Relevance
“…Gillmann et al determined considerable outcome predictability for the second eye based on the outcome after XEN45 Gel Stent implantation (Allergan, Dublin, California) in the first eye 2 . Similar observations were also made by Rosentreter et al in patients bilaterally treated with cataract surgery combined with trabecular aspiration 3 …”
Section: Introductionsupporting
confidence: 87%
“…Gillmann et al determined considerable outcome predictability for the second eye based on the outcome after XEN45 Gel Stent implantation (Allergan, Dublin, California) in the first eye 2 . Similar observations were also made by Rosentreter et al in patients bilaterally treated with cataract surgery combined with trabecular aspiration 3 …”
Section: Introductionsupporting
confidence: 87%
“…Pre- and postoperative antiglaucomatous medication was classified according to a medication score [17]. Surgical (absolute) success was defined as an IOP of 18 mm Hg or lower and a relative decrease of 20% or more compared to the preoperative IOP, without any additional glaucoma surgery or medication.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Only a few studies have described the outcomes of the fellow eye after glaucoma surgery. Predictive values for trabecular aspiration and trabectome surgery have been reported [ 15 , 16 ]. Upon filtering surgery investigations, Mietz et al showed similar trends in the success rate of fellow eyes after trabeculectomy [ 1 ].…”
Section: Discussionmentioning
confidence: 99%